2015
DOI: 10.1093/annonc/mdv032
|View full text |Cite
|
Sign up to set email alerts
|

Non-intercepted dose errors in prescribing anti-neoplastic treatment: a prospective, comparative cohort study

Abstract: Non-intercepted prescribing dose errors occurred in <2% of the prescriptions. The parallel CPOE system did not significantly reduce the overall risk of dose errors, and although it reduced the risk of calculation errors, it introduced other errors. Strategies to prevent future prescription errors could usefully focus on integrated computerised systems that can aid dose calculations and reduce transcription errors between databases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 19 publications
0
28
2
4
Order By: Relevance
“…For that purpose, we compared two groups, with and without PIs, during the same period. Gender and age were not significantly different from one group to another, as opposed to what was described by Mattsson et al., who found that prescriptions for men had fewer errors than those for women . The authors explained this result by the difference between disease in men and women and the related drugs used in each case.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…For that purpose, we compared two groups, with and without PIs, during the same period. Gender and age were not significantly different from one group to another, as opposed to what was described by Mattsson et al., who found that prescriptions for men had fewer errors than those for women . The authors explained this result by the difference between disease in men and women and the related drugs used in each case.…”
Section: Discussioncontrasting
confidence: 57%
“…Finally in two hospitals, Mattsson et al. estimated that 1.7% of anticancer drug prescriptions were erroneously administered without being intercepted …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous literature regarding error reduction through novel technology highlighted that the use of CPOE may introduce new types of errors . The first CPOE system used at FUMC was implemented in 2006.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature regarding error reduction through novel technology highlighted that the use of CPOE may introduce new types of errors. 10,26 The first CPOE system used at FUMC was implemented in 2006. The new-generation ordering tool is developed from the previously used software and thus benefits from the longterm experience of its application in clinical practice.…”
Section: Discussionmentioning
confidence: 99%